Understanding the Olympics - Horne, John 1955-; Whannel, Garry (Routledge, Taylor & Francis Group, 2016)
The Olympic Games is unquestionably the greatest sporting event in the world, with billions of viewers across the globe. How did the Olympics evolve into this multi-national phenomenon? How can the Olympics help us to understand the relationship between sport and society? What will be the impact and legacy of the 2016 Olympics in Rio? Now in a fully revised and updated new edition that places Rio 2016 in the foreground, this book answers all these questions by exploring the social, cultural, political, historical and economic context of the Games. This book presents the latest research on the Olympics, including new material on legacy, sustainability and corruption, and introduces the reader to all of the key themes of contemporary Olympic studies.